SISTEM PEMERINTAHAN DI DESA MAJANNANG KECAMATAN PARIGI KABUPATEN GOWA - Artati Angraeni putri; Tenripadang, Andi; Sakka, Abdul Rahman (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2023)
This study aims to determine the government system applied in Majananng Village, Parigi District, Gowa Regency. The type of research used is qualitative research with normative juridical and normative theological approaches. The results of this study show that the government system currently implemented in Majannang Village still refers to the system regulated in Law Number 6 of 2014 concerning Villages, both in the process of selecting village heads, authority, finance, and the formation of village regulations, including village government administration tools, such as village heads, village officials, village consultative bodies, and village community institutions. In practice, Majannang Village is still held democratically by involving the community in every decision-making, either directly or through representatives. so that in principle, the Majannang Village government system is no different from the village government system in general.